Antimicrobial Susceptibility Pattern of Uropathogens Isolated at a Private Hospital in Khulna, Bangladesh - Faroque, Abdullah Al; Hossain, Md Mokter; Amin, Abu Md Mayeenuddin Al; Muhammad Ashraful Kabir; Mahabuba Khatun; Jiban Nesa; Huq, Md Zahirul (Mediscope, 2024)
Background & objectives: Urinary tract infection (UTI) is one of the most common infectious diseases affecting all age & sex groups, causing significant morbidity & mortality with a substantial economic burden. Due to the irrational empiric use of antibiotics, resistance is increasing at an alarming rate. Bacteria causing UTIs & their antimicrobial susceptibility pattern varies among different areas & changes frequently over time. This study aimed to identify microorganisms causing UTI at a private hospital in the southern part of Bangladesh & to determine their sensitivity pattern towards commonly used antibiotics. Methods: A cross-sectional study was conducted in the clinical pathology & microbiology laboratory at Islami Bank Hospital (IBH), Khulna during the period of January’2021 to July’2021. Clean catch midstream urine samples (MSU) from 221 clinically suspected UTI cases of all age & sex groups were included in the study. Uropathogens were isolated & identified by standard microbiological techniques & susceptibility was determined by Kirby Kirby-Bauer disc diffusion method. Results: Among 221 suspected UTI cases, 108 (48.8%) were positive for urine culture, of which 103 (95.37%) showed antimicrobial growth. The majority 75 (69.4%) of the culture-positive cases were female. E. coli 50(44.24%) was the most predominant bacterial isolate, followed by Klebsiella 18(15.92%) & Enterococcus 16(14.15%). All Isolated gram-positive cocci (GPC) showed very high sensitivity to Vancomycin (83.3% to 100%), Linezolid (87.5% to 100%) & moderate sensitivity to Meropenem (66.7% to 75%). However, they showed relatively lower sensitivity to Ciprofloxacin, Doxycycline, Gentamicin, and Amoxiclav & very poor sensitivity to Nitrofurantoin (31.3% to 50% only). Levofloxacin had relatively better sensitivity against GPC (S. aureus- 83.3% & CONS- 75%), except Enterococcus. All gram-negative bacilli (GNB) showed a very good sensitivity towards Amikacin & Meropenem, ranging from 77.8% to 100%. E. coli & Pseudomonas were highly sensitive to Piperacillin-Tazobactam (90% & 88.9% respectively). GNB were poorly sensitive to commonly used 3rd generation cephalosporins, Azithromycin, Amoxiclav & Ciprofloxacin. Except for Pseudomonas & Klebsiella, Levofloxacin showed relatively good sensitivity against other GNB. Nitrofurantoin showed lower sensitivity against GNB, except for Pseudomonas (66.7%) & Enterobacter (75%). Conclusion: E. coli remains the most predominant uropathogen. Vancomycin, linezolid, Levofloxacin & Meropenem were very effective against GPC whereas Amikacin, Piperacillin- tazobactam & Meropenem showed good responses against GNB. Empiric antibiotics must be selected based on the current antibiogram of uropathogens in a particular area to prevent the increasing trends of antimicrobial resistance. Mediscope 2024;11(1): 01-12